2007
DOI: 10.1590/s1413-70542007000200025
|View full text |Cite
|
Sign up to set email alerts
|

Influência da embalagem na vida útil de presuntos fatiados

Abstract: RESUMOVisou-se com este trabalho, comparar a vida útil de presunto fatiado sem capa de gordura (condicionadas à temperatura entre -1 e 4ºC), usando os tratamentos: sistema de embalagem a vácuo (EV) e sistema de embalagem com atmosfera modificada (AM) (50% de N 2 e 50% de O 2 ), com os laminados flexíveis PET/PEBDL (AM1) e PVDC/EVA/PEBDL (AM2) sobre os parâmetros microbiológicos e físico-químicos, por 35 dias. As análises realizadas foram: contagem padrão em placas (CCP), contagem de fungos (CF), pH e umidade. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
2
2
2
3
Order By: Relevance
“…Fachinello; Casaril (2013) found counts of aerobic mesophilic microorganisms of 2.5×10 to 2.6×10 4 CFU g -1 in sliced hams marketed in Francisco Beltrão, and most of them were inadequate according to the count used by Bressan et al (2007). Pedroso et al (2016) found counts of 10 3 to 10 6 CFU g -1 , which are similar counts to those found in the present study.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Fachinello; Casaril (2013) found counts of aerobic mesophilic microorganisms of 2.5×10 to 2.6×10 4 CFU g -1 in sliced hams marketed in Francisco Beltrão, and most of them were inadequate according to the count used by Bressan et al (2007). Pedroso et al (2016) found counts of 10 3 to 10 6 CFU g -1 , which are similar counts to those found in the present study.…”
Section: Resultssupporting
confidence: 86%
“…These microorganisms can cause unwanted changes of taste and odor and produce mycotoxins or secondary metabolites that accumulate in the body of consumers and can cause health problems due to its toxic and deleterious effects (SOUZA et al, 2017). Bressan et al (2007) recommend maximum counts of molds and yeasts of 10 2 CFU g -1 , a value that is lower than those found in the present work. Serio et al (2009) evaluated the microbiological quality of refrigerated sliced hams marketed in Fortaleza, CE, Brazil, and found similar results for deteriorating molds and yeasts, with counts of 10 5 CFU g -1 for all samples.…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…Entretanto, no presente estudo, alguns consumidores pareciam dispostos a pagar mais por um produto diferenciado (20,8% do total), o que pode refletir na presença de participantes de renda familiar mensal superior a 20 salários mínimos. Além disso, o crescimento da preocupação com o ambiente e com o consumo de alimentos mais seguros também pareceu ser um fator de favorecimento à procura pelo café orgânico, de preço superior ao convencional, fato também observado por Bressan et al (2007) e Hearty et al (2007). Alvensleben & Altman (1987) observaram que o consumo de alimentos orgânicos é relacionado à diminuição da confiança na qualidade de alimentos convencionais e num aumento da preocupação com a saúde, o que reafirma as respostas encontradas com o estudo com os consumidores de café.…”
Section: (Recebido Em 22 De Fevereiro De 2007 E Aprovado Em 3 De Junhunclassified
“…The same study emphasized that the pH value of the product decreased over time due to a number of factors, such as the growth of lactic bacteria and the consequent production of acids throughout the storage period. Meatloaves with pH above 6 are characterized as a perishable product, therefore they are recommended to be stored using a vacuum-packaging system or under modified atmosphere (Bressan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%